Reengineering of Proxy Logging Monitoring System in XYZ Institution - Dharmayanti, Dian; Mukharil Bachtiar, Adam; Ahmad, F (Universitas Komputer Indonesia, 2024)
This research was conducted to assist the head of the IT Operational & Network Education Division of the XYZ institution to reengineering the internet usage monitoring system. This monitoring system is reengineered so that query performance becomes better and the information presented is easily understood by the user. Reengineering the old system will produce a system model that is more in line with the requirements of the current system. The steps taken in this study, analysis of the monitoring system case domain, data analysis, data visualization reengineering, internet use monitoring system reengineering, software implementation and testing. In addition, testing the performance of the query system and usability testing for users from the new visualization results as the output of this study. Reengineering the internet usage monitoring system is a solution to improve query performance and make it easier for users to understand the information presented